2016
DOI: 10.1016/j.cpr.2016.02.002
|View full text |Cite
|
Sign up to set email alerts
|

The use of safety-seeking behavior in exposure-based treatments for fear and anxiety: Benefit or burden? A meta-analytic review

Abstract: There is a longstanding debate whether allowing safety-seeking behaviors (SSBs) during cognitive-behavioral treatment hampers or facilitates the reduction of fear. In this meta-analysis, we evaluate the impact of SSBs on exposure-based fear reduction interventions. After filtering 409 journal articles, 23 studies were included for systematic review of which 20studies were coded for meta-analysis. For each study, the Standardized Mean Difference (SMD or Hedges' g) of self-reported fear was calculated at post-in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 58 publications
1
39
0
1
Order By: Relevance
“…A prior learning history that includes the opportunity to engage in avoidance thus not only maintains the threatvalue of previously safe stimuli but also increases generalized threat perception. Such findings indicate that the (over-)judicious use of safety behaviors in exposure-based treatment for excessive threat-avoidance should be closely monitored (Blakey & Abramowitz, 2016;Meulders, Van Daele, Volders, & Vlaeyen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A prior learning history that includes the opportunity to engage in avoidance thus not only maintains the threatvalue of previously safe stimuli but also increases generalized threat perception. Such findings indicate that the (over-)judicious use of safety behaviors in exposure-based treatment for excessive threat-avoidance should be closely monitored (Blakey & Abramowitz, 2016;Meulders, Van Daele, Volders, & Vlaeyen, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some research has shown that safety behaviors can even enhance treatment outcomes (Goetz & Lee, ). Highlighting these discrepant findings, in a recent review of the impact of safety behaviors on exposure therapy, Meulders and colleagues () speculated that safety behaviors may be burdensome when used to avoid feared consequences, but beneficial when used to facilitate goal achievement. Taken together, these contradictory findings indicate that there is still more to understand about the role of safety behaviors in the etiology, maintenance, and treatment of anxiety.…”
Section: Introductionmentioning
confidence: 99%
“…Avoidance is one particularly prominent behavioral pattern associated with anxiety disorders, and people with anxiety disorders often engage in avoidance of external threats and internal experiences, such as negative thoughts/feelings (American Psychiatric Association, 2013). Avoidance may limit completion of exposure therapy (Zayfert et al, 2005) and even interfere with the likely success of such treatment (Meulders, Van Daele, Volders, & Vlaeyen, 2016). Avoidance may also paradoxically increase self-reported fear, while excessive avoidance is likely to facilitate relapse of anxiety symptoms and coping strategies after therapy (Craske, Hermans, & Vervliet, 2018;Craske et al, 2008;Hermans et al, 2006).…”
mentioning
confidence: 99%